KARAKTERISTIK INDIVIDU, SOSIAL EKONOMI, BUDAYA DAN KESEHATAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA INDUSTRI KECIL DI KOTA MAKASSAR - Baharuddin Semmaila (EKUITAS (Jurnal Ekonomi dan Keuangan), 2008)
This research was to identify the working hours and productivity of labors from Bugis, Toraja, and Makassar in the small industries. In detail, the aims of the research were to know: 1) the influence of individual characteristic, health status, work environment and work ethos (spirit) toward the work productivity of the small industry labors; 2) the differences  of the work productivity among ethnics in the small industries; and 3) the variables which have dominant influence toward the labors’ work productivity in the small industries. The population of this  research were  3135 labors from  garment  and furniture ready-made industries, and the samples were 302 labors. The respondents were workers and employers. The data were analyzed using multiple linear regression with SPSS and AMOS programs and then the results were  combined with the qualitative analysis. The research findings are: 1) the independent variables which influence significantly toward the work productivity of the  small industry workers are work experience,  dependency ratio, health status, weekly wages, work environment and work ethos. While the variables which do not influence the productivity  are workers’ age, sex and length of education. The independent variables which influence dominantly  toward the labor productivity are wages and health status. Good health status may indicate the increase of the productivity. And there are the significant differences of work  productivity among  labors from Bugis, Toraja, and Makassar because of their cultural effects.